Retrograde pylorogastric intussusception - Case report and review - Efrat Avinadav; Hagit Poran Feldman; Eyal Zifman; Yaniv Lakovsky; Enrique N. Freud (Elsevier, 2016)
A case of gastric outlet obstruction in an infant due to retrograde intussusception of the pylorus into the stomach is presented. This anomaly is extremely rare, with almost no reports in the literature. The patient underwent formal Heineke-Mikulicz pyloroplasty with an uneventful recovery and resumed full enteral feeding.